2019
DOI: 10.29298/rmcf.v3i11.517
|View full text |Cite
|
Sign up to set email alerts
|

EVALUACIÓN DE UNA PLANTACIÓN DE Pinus greggii Engelm. CON DOS ESPACIAMIENTOS

Abstract: Las plantaciones forestales en la Sierra Purhépecha, Michoacán, presentan bajos incrementos en altura y diámetro; así como en supervivencia, debido a que se establecieron sin un objetivo específico, con una elección inadecuada de especies, densidades incorrectas en relación con la capacidad productiva de los terrenos, y carecen de seguimiento. La escasa información sobre el crecimiento y desarrollo de las plantaciones con especies exóticas motivó la realización del presente estu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In general, the growth variables (DB, ND and TH) as a function of age had a positive behavior, that is to say, as the age of the reforestation increases, it also increases DB, ND and TH. Muñoz et al, [22] also found that the height and normal diameter of trees increased with age in a Pinus greggii plantation in the Sierra Purépecha in Michoacán, Mexico. Figure 2 shows the average TH of the trees by age and their standard error.…”
Section: Effect Of Age On the Growth Of Pinus Greggiimentioning
confidence: 88%
“…In general, the growth variables (DB, ND and TH) as a function of age had a positive behavior, that is to say, as the age of the reforestation increases, it also increases DB, ND and TH. Muñoz et al, [22] also found that the height and normal diameter of trees increased with age in a Pinus greggii plantation in the Sierra Purépecha in Michoacán, Mexico. Figure 2 shows the average TH of the trees by age and their standard error.…”
Section: Effect Of Age On the Growth Of Pinus Greggiimentioning
confidence: 88%
“…Sin embargo, las reforestaciones efectuadas con ayuda de PROBOSQUE, han tenido resultados poco promisorios, debido a que el porcentaje de sobrevivencia de las plantas en diversas regiones del Estado de México, ha sido del 38% (Torres, 2021), porcentaje inferior al rango aceptable de 50-60% en las especies de pinos más utilizadas, como Pinus greggii (Muñoz et al, 2012). Actualmente, PROBOSQUE busca elevar los porcentajes de sobrevivencia, implementando programas de incentivos económicos a los predios reforestados que tengan más del 40% de sobrevivencia (PROBOSQUE, 2023b).…”
Section: Introductionunclassified
“…It is necessary to promote genetic improvement programs that allow the safeguarding, propagation and improvement of genotypes of high ecological, commercial and cultural value (Neale & Kremer, 2011;Wheeler et al, 2015;Gray et al, 2016). Likewise, genetic improvements may allow for the obtaining of better survival and productivity results in commercial forest plantations, which in Mexico have an approximate annual mortality rate of 45% (Muñoz-Flores et al, 2012;Rosales-Mata et al, 2015). In northern Mexico and the southern United States of America, P. engelmannii and P. arizonica Engelm var.…”
Section: Introductionmentioning
confidence: 99%